Mononitrate Isosorbide as an Adjunctive Therapy in Schizophrenia: A Randomized Controlled Crossover Trial. Issue 3 (May 2021) - Guimarães, Tiago M.; Guimarães, Mara R. C.; Oliveira, Ícaro A. F.; Leoni, Renata F.; Santos, Antonio C.; Dursun, Serdar M.; Crippa, Jose A.S.; Bressan, Rodrigo A.; Machado-de-Sousa, João Paulo; Lacerda, Acioly L. T.; Hallak, Jaime E. Cecílio
Abstract: Background: Schizophrenia is a complex disabling mental disorder, and many patients present poor response to available treatments. Accumulating evidence about the role of the glutamate/nitric oxide pathway in mediating the positive and negative symptoms of schizophrenia suggests potential benefits of drugs that modulate this system. The aim of this study was to test the efficacy of isosorbide mononitrate (ISMN) as an adjunctive therapy for symptomatic outpatients with schizophrenia. Methods: This was a 2-month randomized, double-blind, placebo-controlled trial with 24 schizophrenia patients. Participants were treated with ISMN 50 mg for 1 month and placebo for another month in a crossover design. The Positive and Negative Syndrome Scale (PANSS), Clinical Global Impression Scale, Global Assessment of Functioning, and MATRICS Cognitive Consensual Battery were used for symptom assessment and arterial spin labeling was used to assess brain activation patterns. Results: We found significant differences in the total, general, and positive subscales of the PANSS, Global Assessment of Functioning scores, and Clinical Global Impression scores during treatment with ISMN relative to placebo. No treatment effects were found comparing scores in the MATRICS Cognitive Consensual Battery and the negative subscale of the PANSS between the active and placebo conditions. A post hoc analysis of neuroimaging data showed reduced activity in the thalamus in subgroup of patients with severe psychopathology. Conclusions: Schizophrenia patients with persistent symptoms showed significant improvement after 4 weeks of treatment with ISMN 50 mg/d compared with placebo. Isosorbide mononitrate added beneficial effects to antipsychotic treatment in terms of positive symptoms and functioning. Abstract : Supplemental digital content is available in the text.